INNER COMPETENCIES FOR INSPIRING TEACHER: A LITERATURE REVIEW - Loly Novita (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Being a teacheris not really easy. There are steps he must take into account to createsuccessful teaching process. During the teaching process, the teacher focusesnot only onpreparing and delivering teaching materials, but also on how to organize the students dothe class activities individually or groups. However, the teacher also needs to have innercompetencies to make his teaching successful. These competencies cover his ability inunderstanding the truth of learning, knowing the learning principles, getting ideas of thetruth of teaching, and finding out his students’ character. Improving his innercompetencies of teaching continuously will lead him to create smooth teaching process Itwill of course give big influences for the success of teaching and learning. The teacher canbe a better and wiser person while facing difficulties in conducting teaching duties.Meanwhile, he can bring his students achieve better in learning.Keywords–– Inner competencies, the truth of learning, the learning principles, the truth ofteaching, and knowing the students’ character.